Polymorphisms of selected Xenobiotic Genes contribute to the development of Papillary Thyroid Cancer susceptibility in Middle Eastern population - Al-Nuaim Abdulrahman; Al-Sanea Osama; Al-Dayel Fouad; Siddiqui Shakaib U; Bu Rong; Abubaker Jehad; Al-Rasheed Maha; Ibrahim Muna; Siraj Abdul K; Uddin Shahab; Al-Kuraya Khawla (BMC, 2008)
Abstract Background The xenobiotic enzyme system that enables us to detoxify carcinogens exhibits identifiable genetic polymorphisms that are highly race specific. We hypothesized that polymorphisms of these genes may be associated with risk of thyroid cancer. To evaluate the role of genetic polymorphisms of xenobiotic genes in thyroid cancer, we conducted a hospital-based case-control study in Saudi population. Methods 223 incident papillary thyroid cancer cases and 513 controls recruited from Saudi Arabian population were analyzed for the association between polymorphisms in genes encoding folic acid metabolizing enzymes MTHFR and six xenobiotics-metabolizing enzymes including CYP1A1 T3801C, C4887A, GSTP1 A1578G, C2293T, GSTM1, GSTT1, NAT2 G590A, NQO*1 C609T, using PCR-RELP. Results Among selected genes, CYP1A1 C4887A genotypes CA, AA and variant allele A demonstrated significant differences and greater risk of developing thyroid cancer comparing to wild type genotype CC (CA vs. CC; p < 0.0001, OR = 1.91, 95% CI = 1.36-2.70, AA vs. CC; p < 0.001, OR = 3.48, 95% CI = 1.74-6.96 and CA+AA vs. CC; p < 0.0001, OR = 2.07, 95% CI = 1.49-2.88). GSTT1 null showed 3.48 times higher risk of developing thyroid cancer (p < 0.0001, 95% CI = 2.48-4.88) while GSTM1 null showed protective effect (p < 0.05, OR = 0.72, 95% CI = 0.52-0.99). Remaining loci demonstrated no significance with risk. Conclusion Of the 9 polymorphisms screened, we identified GST, GSTM1 and CYP1A1 C4887A, may be of importance to disease process and may be associated with papillary thyroid cancer risk in Saudi Arabian population.